2021
DOI: 10.15414/jmbfs.2681
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Study on Rat Isolated Hepatocytes and Possible Protection of Ginger (Extract and Nanoparticles) Against Acetaminophen Toxicity

Abstract: Ginger is one of most important medicinal plants which used in variable diseases. Recently, ginger nanoparticles have been isolated from ginger extract and exhibited anti-apoptotic activity, hepatoprotective effect against alcohol and may effectively reduce colitis. Our study aimed to compare between the effect of ginger extract and ginger nanoparticles at concentration of 60 µg/ml against hepatotoxicity caused by acetaminophen (APAP; N-acetyl-para-aminophenol) at concentration of 0.1 mg/ml using primary isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…In the present study, we used Ccl4 in inducing liver damage as significant fibrosis occurred after two-four weeks from exposure to it (27) . Our results agreed with Abdelgayed et al (28) who reported that ginger nanoparticles gave better therapeutic results through reducing the parameters of liver toxicity and providing a safe method for drug delivery in addition to excellent biocompatibility relative to ginger extract. Motawi et al (29) noticed that ethanol extract of ginger had more potent effect than silymarin on liver weight and Bencheikh et al (30) mentioned that Ccl4 toxicity led to alteration in collagen synthesis and deposition of collagen I and III in liver leading to disturbance of normal architecture and increase liver weight while silymarin inhibited that.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we used Ccl4 in inducing liver damage as significant fibrosis occurred after two-four weeks from exposure to it (27) . Our results agreed with Abdelgayed et al (28) who reported that ginger nanoparticles gave better therapeutic results through reducing the parameters of liver toxicity and providing a safe method for drug delivery in addition to excellent biocompatibility relative to ginger extract. Motawi et al (29) noticed that ethanol extract of ginger had more potent effect than silymarin on liver weight and Bencheikh et al (30) mentioned that Ccl4 toxicity led to alteration in collagen synthesis and deposition of collagen I and III in liver leading to disturbance of normal architecture and increase liver weight while silymarin inhibited that.…”
Section: Discussionsupporting
confidence: 92%